PROSES PENGASUHAN IBU BEKERJA - Adi Wibowo; Satih Saidiyah (UIN Sunan Kalijaga, 2013)
This study was to purpose the parenting process of working mother. This study was done at Guntur, Bener, Purworejo. Parenting process that was defned in this study was any act of working mother to give attention, time, and support which can satisfy the physychal, mental, and social need of children.. The theory used in this study was a theory about parenting and the role of mother in household. This study used a qualitative method which was case study approach. The data was collected by interview and observational techniques, and also documentation. The informants in this study were mother who work as farmer, teacher, and merchants. This study found that the children parenting planning started in the womb. There are varioust ritual of customery and religion in welcoming birth of a child. During the process of parenting, the three informants took parenting and still worked. In addition, family involvement be a contributing factor supporting the succes of talking about parenting. The three informants revealed that they did not have a lot of obstacles in parenting their children. Their obstacles were just education for their children, the demands of work and children’s health conditions. It’s that makes the process of working mother parenting become so interesting.